- #1

quick

- 42

- 0

http://img66.imageshack.us/img66/9784/prob17zo.jpg [Broken]

j*omega = s

so for a, i got Vo = Vi * (sL/(sL+R+1/sc))

so H(s) = sL/(sL+R+1/sc) and i multiplied it by s/s to get rid of s in in denominator of the 1/sc term to get s^2*L/(s^2*L+Rs+1/c)

is this correct?

for the second one i got Vo=Vi*(1/sc)/(R*sL/R+sL)+1/sc. i did a similar thing by multiplying by s/s.

any suggestions would be appreciated.

j*omega = s

so for a, i got Vo = Vi * (sL/(sL+R+1/sc))

so H(s) = sL/(sL+R+1/sc) and i multiplied it by s/s to get rid of s in in denominator of the 1/sc term to get s^2*L/(s^2*L+Rs+1/c)

is this correct?

for the second one i got Vo=Vi*(1/sc)/(R*sL/R+sL)+1/sc. i did a similar thing by multiplying by s/s.

any suggestions would be appreciated.

Last edited by a moderator: